Physical Activity Among Adolescents in an East Malaysian Rural Indigenous Community: Exploring the Influence of Neighborhood Environmental Factors - Rosalia, Saimon; Choo, Wan Yuen; Chang, Kam Hock; Ng, Chirk Jenn; Awang, Bulgiba (Sage Publication, 2015)
This study explores the rural environmental factors that influence adolescents’ participation in physical activities (PA). Thirty-six indigenous adolescents, aged 13 to 17 years from rural communities of East Malaysia were involved in the photovoice procedures: photo-taking, selecting, contextualizing, and codifying themes. Despite being endowed with natural resources such as river, forest, hills, and so on, the adolescents and the community did not capitalize on these rich resources to promote and engage in PA. Poor maintenance of natural resources, the lack of pedestrian infrastructures and road safety, the lack of PA facilities, and negative perception of ancestors’ agricultural activities were among factors that constrained adolescents’ PA. Although basic amenities such as play spaces and pedestrian infrastructures are necessary to increase adolescents’ PA, any intervention should make the most of the natural resources, which are cheaper, environment friendly, and sustainable.